Pathways to Science and Engineering Bachelor's Degrees for Men and Women - Joscha Legewie; Thomas A. DiPrete (Sociological Science, 2014)
Despite the striking reversal of the gender gap in educational attainment and the near–gender parity in math performance, women pursue science and engineering (S/E) degrees at much lower rates than their male peers do. Current efforts to increase the number of women in these fields focus on different life-course periods but lack a clear understanding of the importance of these periods and how orientations toward S/E fields develop over time. In this article, we examine the gendered pathways to a S/E bachelor's degree from middle school to high school and college based on a representative sample from the 1973 to 1974 birth cohort. Using a counterfactual decomposition analysis, we determine the relative importance of these different life-course periods and thereby inform the direction of future research and policy. Our findings confirm previous research that highlights the importance of early encouragement for gender differences in S/E degrees, but our findings also attest to the high school years as a decisive period for the gender gap, while challenging the focus on college in research and policy. Indeed, if female high school seniors had the same orientation toward and preparation for S/E fields as their male peers, the gender gap in S/E degrees would be closed by as much as 82 percent.
Keywords: 320; gender; education; STEM fields